2004
DOI: 10.1111/j.1365-2745.2004.00964.x
|View full text |Cite
|
Sign up to set email alerts
|

How open were European primeval forests? Hypothesis testing using palaeoecological data

Abstract: Summary 1The Vera hypothesis that large herbivores maintained an open landscape in the primeval landscape of lowland Europe is tested using palaeoecological data. The hypothesis suggests that the high abundance of Quercus and Corylus apparent in European pollen diagrams could not have derived from a landscape dominated by closed canopy forests. If natural forest landscapes were indeed more open, current forest conservation management policy across Europe would need to be reconsidered. 2 Relative proportions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
164
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(171 citation statements)
references
References 48 publications
3
164
0
4
Order By: Relevance
“…Temperate grasslands are among the most speciesrich vegetation types in Europe and have great conservation value (Eriksson et al 2002;Poschlod and WallisDeVries 2002;. They usually endure due to moderate human-induced disturbances such as animal husbandry, mowing and collection of firewood (Settele and Henle 2003) and are classified as 'semi-natural ' (van Dijk 1991), although their flora is spontaneous (Svenning 2002;Mitchell 2005). Likewise, European heathlands and shrublands are semi-natural ecosystems which have been coevolving for millennia with human societies and represent a distinctive set of European habitats for their biodiversity, and aesthetic and cultural values (Wessel et al 2004;Quétier et al 2007;de Bello et al 2009).…”
Section: Selection Of European Terrestrial and Freshwater Ecosystemsmentioning
confidence: 99%
“…Temperate grasslands are among the most speciesrich vegetation types in Europe and have great conservation value (Eriksson et al 2002;Poschlod and WallisDeVries 2002;. They usually endure due to moderate human-induced disturbances such as animal husbandry, mowing and collection of firewood (Settele and Henle 2003) and are classified as 'semi-natural ' (van Dijk 1991), although their flora is spontaneous (Svenning 2002;Mitchell 2005). Likewise, European heathlands and shrublands are semi-natural ecosystems which have been coevolving for millennia with human societies and represent a distinctive set of European habitats for their biodiversity, and aesthetic and cultural values (Wessel et al 2004;Quétier et al 2007;de Bello et al 2009).…”
Section: Selection Of European Terrestrial and Freshwater Ecosystemsmentioning
confidence: 99%
“…Determination of human activities from pollen diagrams usually involves a combination of evidences, including changes in vegetation composition and grassland indicator species (Ren 2000;Berglund 2003). From vegetation modelling based on pollen data, studies of past landscape openness have been performed, e.g., for southern Sweden (Sugita et al 1999), for China north of the Yangtze River (Ren & Beug 2002) and recently on a European level (Mitchell 2005).…”
Section: Sources Of Past Climatementioning
confidence: 99%
“…Although it has been suggested that during the early Holocene medium-size herbivores (red deer, elk, wild pigs and aurochs) would have helped to reduce the forest canopy (Vera, 2000), a more recent study from Ireland suggests that these dense forests would have been maintained despite the herbivores (Mitchell, 2004;Moore, 2005). The absence of elephant and rhinoceros in these environments during the Holocene is the critical factor, allowing the persistence of dense woodland.…”
Section: Vegetationmentioning
confidence: 99%